Fractal nature of internet traffic - Lent, Ricardo (1998)
In this article we show the results of the analysis of 18 million Internet datagrams collected between April 1996 and June 1997 in one of the networks of the Peruvian Scientific Network. It is demonstrated that the flow of TCP/IP packets present an asymptotically Self-similar (fractal) nature analogous to that found in Ethernet local area networks [1] and that differs from that predicted by traditional traffic models based on Markov processes. and semi-Markov like Poisson.